Emerging immunotherapeutic strategies targeting telomerases in genitourinary tumors. (November 2018) - Carrozza, Francesco; Santoni, Matteo; Piva, Francesco; Cheng, Liang; Lopez-Beltran, Antonio; Scarpelli, Marina; Montironi, Rodolfo; Battelli, Nicola; Tamberi, Stefano
Highlights: Telomerase activity is essential for the pathogenesis of genitourinary tumors. Telomerase degraded fragments on tumor cells allow the recognition by immune cells. Active and passive immunotherapies are under evaluation in genitourinary tumors. Abstract: Telomerase activity and telomere length are essential for the pathogenesis of several human diseases, including genitourinary tumors. Telomerase constitutes a complex system that includes human telomerase reverse transcriptase (hTERT), human telomerase RNA component (hTR) and telomerase associated protein 1 (TEP1), which are overexpressed in tumor cells compared to normal cells and are involved in the carcinogenesis and progression of renal cell carcinoma (RCC), bladder (BC) and prostate cancer (PCa). In addition, telomerase degraded peptide fragments expressed on the surface of tumor cells lead to their recognition by immune cells. On this scenario, in vitro and in vivo studies have shown effective anti-tumor activity of hTERT-tailored strategies in genitourinary tumors, including active immunotherapy with hTERT-peptide vaccines and passive immunotherapy with hTERT-transduced T cell infusion. This review emphasizes the role of telomerase in the carcinogenesis and progression of genitourinary tumors, thus underlying the potential of emerging telomerase-tailored immunotherapies in these patients.